Genitourinary injuries after traffic accidents: Analysis of a registry of 162, 690 victims. Issue 6 (June 2017) - Terrier, Jean-Etienne; Paparel, Philippe; Gadegbeku, Blandine; Ruffion, Alain; Jenkins, Lawrence C.; N'Diaye, Amina
Abstract : BACKGROUND: Traffic accidents are the most frequent cause of genitourinary injuries (GUI). Kidney injuries after trauma have been well described. However, there exists a paucity of data on other traumatic GUI after traffic accidents. The objective of this study was to analyze the frequency and type of all GUI, by user category, after traffic accidents. METHODS: Patient cases were extracted from the trauma registry of the French department of Rhone from 1996 to 2013. We assessed the urogenital injuries presented by each of road user's categories. Severity injuries were coded with the Abbreviated Injury Scale and the Injury Severity Score. Kidney trauma was mapped with the classification of the American Association for the Surgery of Trauma. Multivariate prediction models were used for analysis of data. RESULTS: Of 162, 690 victims, 963 presented with GUI (0.59%). 47% were motorcyclists, 22% were in a car, 18% on bicycles, and 9% were pedestrians. The most common organ injury was kidney (41%) followed by testicular (23%). Among the 208 motorists with a GUI, kidney (70%), bladder (10%), and adrenal gland (9%) were the most frequent lesions. Among the 453 motorcyclist victims with GUI, kidney (35%) and testicular (38%) traumas were the most frequent and 62% of injuries involved external genitalia. There were 175 cyclists with GUI, 70% of injuries involved external genitalia; penile traumas (23%) were the most frequent. In total, there were 395 kidney injuries, most being low grade. According to the American Association for the Surgery of Trauma kidney injuries were grade I, 59%; grade II, 11%; grade III, 16%; grade IV, 9%; grade V, 3%; and indeterminate, 2%. CONCLUSION: GUI is an infrequent trauma after traffic accidents, with kidneys being the most commonly injured. Physicians must maintain a high awareness for external genitalia injuries in motorcyclists and cyclists. LEVEL OF EVIDENCE: Prognostic and epidemiologic study, level III.